2019
DOI: 10.1093/ajh/hpz060
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Association Between Blood Pressure Status and Atrial Fibrillation in an Elderly Chinese Population

Abstract: OBJECTIVE Atrial fibrillation (AF) and hypertension are prevalent chronic disease conditions in the elderly population. In the present cross-sectional study, we investigated the association between blood pressure (BP) and AF in an elderly Chinese population. METHOD Our elderly (≥65 years) subjects were residents recruited from 6 communities in Shanghai from 2006 to 2017. Atrial fibrillation was systematically screened by rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…A cross-sectional study enrolling elderly subjects suggested a negative relationship between SBP and AF prevalence. 29 A similar trend has been observed in other studies that enrolled and followed older subjects who started hemodialysis. 30 In subjects receiving antihypertensive treatment, a J-shaped relationship between SBP and AF was observed.…”
Section: Discussionsupporting
confidence: 81%
“…A cross-sectional study enrolling elderly subjects suggested a negative relationship between SBP and AF prevalence. 29 A similar trend has been observed in other studies that enrolled and followed older subjects who started hemodialysis. 30 In subjects receiving antihypertensive treatment, a J-shaped relationship between SBP and AF was observed.…”
Section: Discussionsupporting
confidence: 81%
“…A considerable cardiovascular burden in northeast China was recently confirmed 9. However, previous studies on AF epidemiology were limited by relatively small sample size,10 non-representative sampling,4 restricted region and population8 or insufficient estimation of AF characteristics 11. Therefore, accurate and comprehensive estimation of the disease burden of AF in northeast China is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Low SBP may indeed increase the risk of AF via chronic coronary ischemia, myocardial proliferation and fibrosis induced by inadequate coronary perfusion which leads to the development of AF. On the other hand, low SBP may be the result of AF or AF-related cardiac structural and functional abnormalities (10,28). Another explanation may be that individuals with higher SBP levels are more likely to receive better clinical care and more usage of antihypertensive medications, which plays an important role in the mutually influenced relationship between hypertension and AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited and conflicting data on the association between AF and the degree of systolic blood pressure (SBP) control in hypertensive patients, especially in patients receiving antihypertensive treatment. Studies were even fewer in Chinese regions (10,11). In the present study, we investigated the relationship between SBP and AF in a group of hypertensive patients in Chinese population with or without antihypertensive medications.…”
Section: Introductionmentioning
confidence: 96%